Publication retrieval system for Bahagian Arkib & Muzium (BAM) UiTM using vector space model / Nor Adzlan Jamaludin - Jamaludin, Nor Adzlan (2011)
Information retrieval and search engines have become an essential aspect in many information systems. In systems which employ large databases, information retrieval becomes more important as it is able to perform better than the standard query search depending on the model used. Currently, the Bahagian Arkib & Muzium (BAM) of UiTM does not have an information search engine for its publication and retrieves information on publication materials manually. The objectives of this project are to create a publication bulletin database for BAM, create a retrieval engine prototype based on the bulletin database and test the functionality of the prototype in retrieving the information on bulletins. A search engine prototype that is based on the vector space model is implemented for the project.